PENILAIAN JENIS GANGGUAN TIDUR DENGAN MEMPERGUNAKAN SKALA TIDUR PADA PENYAKIT PARKINSON - Dewi Gentari*, Bob SW*, Fitri O* , Joedo Prihartono** (Neurona Majalah Kedokteran Neuro Sains, 2009)
BACKGROUND SLEEP DISORDER IS ONE OF THE NONMOTORIC SYMPTOMS OF PARKINSONS DISEASE THAT OFTEN APPEARS BUT RARELY DETECTED PRESERVING AND INCREASING SLEEP QUALITY IS VERY IMPORTANT TO REPAIR THE MOTORIC SYMPTOMS THE AIMS OF THIS STUDY ARE TO KNOW THE TYPES OF SLEEP DISORDER EXPERIENCED PARKINSON PATIENTS AND OTHER FACTORS THAT AFFECT THEM